Post-buckling analysis of GPLs reinforced porous cylindrical shells under axial compression and hydrostatic pressure. (March 2022) - Sun, Guangxin; Zhu, Shengbo; Teng, Rumin; Sun, Jiabin; Zhou, Zhenhuan; Xu, Xinsheng
Abstract: Research works on post-buckling of cylindrical shells under combined loads are usually presented with insufficient accuracy. It is mainly related to the inherent complexity compared to the case subjected to a single load, particularly when the problem is investigated based on the moderately thick shell theory. In the present study, post-buckling analysis of functionally graded graphene platelets reinforced composite (FG-GPLRC) porous cylindrical shells under the action of axial compression and hydrostatic pressure is performed. The main aim is to obtain reasonably accurate post-buckling characteristic quantities of the problem at hand for a wide range of thicknesses. For this purpose, elaborately constructed boundary conditions, complete post-buckling deformation modes, and a unified shell theory, which is efficient and suitable for extremely thin and moderately thick structures, are carefully taken into account. The solutions based on the symmetric and asymmetric post-buckling modes are established by combining an analytical procedure and the Galerkin's method. The obtained results from the present solutions agree well with those of existing theoretical and experimentally observed data. The effects of the geometry and the material properties on the post-buckling behavior and knockdown factor (KDF) of the FG-GPLRC porous cylindrical shell are explored. The discrepancies between the results of the classical thin-walled shell theory and those of the moderately thick shell theory are then explained and discussed in detail. Highlights: Post-buckling of GPLs reinforced porous cylindrical shell under combined loads is precisely analyzed. Solution procedure based on a unified shell theory is suitable for a wide range of shell thickness. Elaborately constructed boundary conditions and complete post-buckling modes are considered. Shear deformations introduced in moderately thick shell theory have a significant impact on post-buckling. KDFs can be predicted accurately by the solutions of symmetric post-buckling modes.